2021
DOI: 10.1159/000514869
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mental Imagery on Prospective Memory: A Process Analysis in Individuals with Amnestic Mild Cognitive Impairment

Abstract: <b><i>Introduction:</i></b> Prospective memory (PM) is a multiphasic cognitive function important for autonomy and functional independence but is easily disrupted by pathological aging processes. Through cognitive simulation of perceptual experiences, mental imagery could be an effective compensatory strategy to enhance PM performance. Nevertheless, relevant research in individuals with amnestic mild cognitive impairment (MCI) has been limited, and the underlying mechanism of the therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…with cognitive impairment) are often encouraged to generate an image that reflects the planned action, with the aim of this image being involuntarily retrieved at the appropriate time. In fact, a recent study showed Preprint v1.0_12.07.2023 https://osf.io/jhs37/ that patients with cognitive impairment who generated mental imagery for an intended action to be taken in the future performed better in later retention, initiation, and execution of the intended action than participants who engaged only in repetitive rehearsal (Cheng et al, 2021). To the extent to which facilitative effects of mental imagery on prospective memory may be driven by involuntary recall of the previously-generated image, factors that increase the likelihood of involuntary recall (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…with cognitive impairment) are often encouraged to generate an image that reflects the planned action, with the aim of this image being involuntarily retrieved at the appropriate time. In fact, a recent study showed Preprint v1.0_12.07.2023 https://osf.io/jhs37/ that patients with cognitive impairment who generated mental imagery for an intended action to be taken in the future performed better in later retention, initiation, and execution of the intended action than participants who engaged only in repetitive rehearsal (Cheng et al, 2021). To the extent to which facilitative effects of mental imagery on prospective memory may be driven by involuntary recall of the previously-generated image, factors that increase the likelihood of involuntary recall (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The correct profiling of the cognitive performance of the patient with MCI will allow choosing the ideal therapeutic interventions. There are several studies evidencing the efficacy of interventions on prospective memory failures in patients with MCI such as enactment and visual imagery (Cheng et al, 2021;Emsaki et al, 2017;Pereira et al, 2015).…”
Section: Discussionmentioning
confidence: 99%